DIURNAL TEMPERATURE RANGE VARIABILITY OVER KARNATAKA, INDIA: SPECTRAL EVIDENCE OF INTERANNUAL AND DECADAL CLIMATE MODES (1958–2024): DIURNAL TEMPERATURE RANGE VARIABILITY OVER KARNATAKA, INDIA - SRINIVASA SASDHAR PONNALURU (The Journal of Research ANGRAU, 2026)
Diurnal temperature range (DTR), defined as the difference between daily maximum andminimum temperatures, is an important indicator of climatic variability and land–atmosphereinteractions. This study examines the temporal variability of DTR over Karnataka, India, usingmonthly temperature data for 1958–2024. Monthly DTR anomalies were analysed using Welchand Lomb–Scargle spectral techniques with statistical significance assessed against an AR(1)red-noise background. The results reveal variability across multiple timescales, includinginterannual (H=2–5 years), sub-decadal (H=8–9 years), and a statistically significant decadalcycle near 16–17 years. Additional low-frequency variability around 30 years indicates gradualclimatic modulation of DTR. These findings highlight the presence of multi-timescale climatevariability influencing diurnal temperature behaviour in southern India, with potential implicationsfor agricultural planning and climate adaptation.